A History of the 'Alawis: From Medieval Aleppo to the Turkish Republic, by Stefan Winter. (11th May 2018) - Berger, Lutz
Abstract : A History of the ʿAlawis: From Medieval Aleppo to the Turkish Republic, by Stefan Winter. Princeton University Press, 2016. Hb. 85.00, ISBN-13: 9780691167787.